Polyhydroxyalkanoates - linking properties, applications and end-of-life options - Koller, Martin (Array, 2020)
When it comes to "bioplastics", we currently notice an immense complexity of this topic, and, most of all, a plethora of contradictory legislations, which confuses or even misleads insufficiently informed consumers. The present article therefore showcases microbial polyhydroxyalkanoate (PHA) biopolyesters as the prime class of “bioplastics” sensu stricto. In particular, biodegradability of PHA as its central benefit in elevating the current plastic waste scenario is elaborated on the biochemical basis: this covers aspects of the enzymatic machinery involved both in intra- and extracellular PHA degradation, and environmental factors impacting biodegradability. Importantly, PHA degradability is contextualized with potential fields of application of these materials. It is further shown how the particularities of PHA in terms of feedstocks, mode of synthesis, degradability, and compostability differ from other polymeric materials sold as "bioplastics", highlighting the unique selling points of PHA as “green” plastic products in the circular economy. Moreover, current standards, norms, and certificates applicable to PHA are presented as basis for a straight-forward, scientifically grounded classification of "bioplastics".